Physiotherapy Management of Hamstring Strain with Ultrasound, Neuromuscular Taping (NMT), and Progressive Isometric Exercise: A Case Report - Rizal, Yose; Putri, Ruswita (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
Hamstring strain is one of the most common injuries in sports, particularly in activities requiring sprinting and sudden acceleration. Effective physiotherapy intervention is essential to facilitate recovery, restore muscle function, and prevent recurrence. A 23-year-old male footballer presented with pain and tightness in the posterior thigh after a sprinting injury. The patient was diagnosed with a grade 2 hamstring strain and sought physiotherapy at Fisiohands Clinic, Pekanbaru, following an initial medical evaluation. The rehabilitation program included ultrasound therapy, neuromuscular taping (NMT), and progressive isometric exercises. Pain reduction, increased flexibility, and improved functional capacity were observed after four weeks of intervention. The patient underwent a structured four-week physiotherapy protocol, including pain management, mobility training, and strengthening exercises. Visual Analogue Scale (VAS), Goniometer and The Lower Extremity Functional Scale (LEFS) were used for evaluation. After four weeks, the patient demonstrated pain reduction (VAS 7 to 2), increased flexibility (45° to 78°), and improved functional performance (LEFS 30 to 65). These findings indicate that ultrasound, NMT, and isometric exercises are effective modalities in acute hamstring strain rehabilitation.